Effective Biosorption of Phosphate Ions from Aqueous Solution Using Fe(III)-Loaded Carboxyl Functionalized Banana Peels - Bhattarai, Pukar; Pant, Naresh; Poudel, Bhoj Raj; Aryal, Ram Lochan (Journal of Nepal Chemical Society, 2026)
Phosphate contamination in water bodies is a major environmental concern due to its role in eutrophication, necessitating the development of low-cost, efficient, and sustainable removal technologies. In this study, an eco-friendly biosorbent was prepared from waste banana peels through saponification followed by Fe(III) loading (Fe(III)-SBP) for effective phosphate ion removal from aqueous solutions. The prepared biosorbent was characterized using FTIR and SEM to confirm functional group modification and surface morphology, while the point of zero charge (pHPZC) was determined to be 6.8. Batch biosorption experiments revealed that phosphate uptake was highly pH-dependent, with a maximum biosorption capacity of 18.51 mg/g at pH 5.34. Equilibrium and kinetic data were best described by the Langmuir isotherm and pseudo-second-order kinetic model, indicating monolayer chemisorption. Competitive ion studies showed negligible interference from chloride and nitrate ions, whereas sulphate and bicarbonate ions significantly inhibited phosphate removal. The adsorbed phosphate was efficiently desorbed using 0.5 M NaOH, demonstrating good regeneration potential of the biosorbent. Overall, the results confirm that Fe(III)-loaded saponified banana peels are an effective, low-cost, and sustainable biosorbent for phosphate removal, highlighting their potential application in wastewater treatment and nutrient pollution control.